Impact of chronic heat stress on digestibility of nutrients and performance of meat type ducks - Horváth, Márta; Babinszky, László (Acta Agraria Debreceniensis, 2017)
The aim of the study is to determine the effect of vitamin and mineral supplement under permanently high environmental temperature (30±1 °C) on the digestibility of nutrients, performance and furthermore the composition of duck meat in the growing period. A total of four hundred mixed sex 14 days old Cherry Valley type hybrid ducks were used for the study. Two experimental diets were formulated in the study (control and vitamin E, C and zinc supplemented diet). Based on the results the following conclusions were drown: the antioxidant defence system plays an important role in the reduction of heat stress generated lipid peroxidation process. Feed additives which have direct or indirect antioxidant effects can reduce the negative effects of heat stress on the ducks performance and meat composition. Digestibility of nutrients (Dry Matter, Crude Protein, Crude Fat) was not affected by antioxidant supplementation under chronic heat stress (30±1 °C). The performance was affected significantly by Vitamin C and E and zinc supplementation under heat stress (P